State policy in the field of employment promotion of NEET category youth - Nurtazina Р.А.; Mukhtarova Н. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2022)
The article is devoted to the consideration of one of the most pressing issues of the socio-economic policy of the states of the world - the promotion of employment and economic activity of NEET youth in the context of the COVID-19 pandemic. As the analysis of labor market indicators at the international level shows, during the period of global economic and political crises, the most vulnerable segment of the population in the face of challenges is the youth. Some experts argue that a young person is twice as likely to not find a job as other age groups. In the long term, the exclusion of some of the youth from the labor market is one of the most serious threats to society. In this regard, the issues of improving state policy measures to support NEET youth are of particular strategic importance for the country. The purpose of the study is to identify effective approaches to the activities of state bodies to promote the employment of youth in the NEET category. In the course of the study, the author identified features and trends in the field of policies to promote youth employment in the NEET category, and also developed recommendations for improving these approaches in Kazakhstan.